Problem Drinking, Alcohol-Related Violence, and Homelessness Among Youth Living in the Slums of Kampala, Uganda - Culbreth, Rachel (International journal of environmental research and public health, 2018)
This paper examines problem drinking, alcohol-related violence, and homelessness among youth living in the slums of Kampala—an understudied population at high-risk for both alcohol use and violence. This study is based on a cross-sectional survey conducted in 2014 with youth living in the slums and streets of Kampala, Uganda (n = 1134), who were attending Uganda Youth Development Link drop-in centers. The analyses for this paper were restricted to youth who reported current alcohol consumption (n = 346). Problem drinking patterns were assessed among youth involved in alcohol-related violence. Mediation analyses were conducted to examine the impact of homelessness on alcohol-related violence through different measures of problem drinking. Nearly 46% of youth who consumed alcohol were involved in alcohol-related violence. Problem drinkers were more likely to report getting in an accident (χ2 = 6.8, df = 1, p = 0.009), having serious problems with parents (χ2 = 21.1, df = 1, p < 0.0001) and friends (χ2 = 18.2, df = 1, p < 0.0001), being a victim of robbery (χ2 = 8.8, df = 1, p = 0.003), and going to a hospital (χ2 = 15.6, df = 1, p < 0.0001). For the mediation analyses, statistically significant models were observed for frequent drinking, heavy drinking, and drunkenness. Interventions should focus on delaying and reducing alcohol use in this high-risk population